Communications Training in Pharmacy Education, 1995-2010 - Wallman, Andy (American Journal of Pharmaceutical Education, 2013)
The role of the pharmacist as a “communicator” of information and advice between patients, other healthcare practitioners, and the community is recognized as a vital component of the responsibilities of a practicing pharmacist. Pharmacy education is changing to reflect this, although the difficulty is in designing a curriculum that is capable of equipping students with the necessary knowledge and skills, using activities that are effective in promoting communication competency. The objective of this review was to identify published, peer-reviewed articles concerning communication training in pharmacy education programs, and describe which communication skills the structured learning activities aimed to improve and how these learning activities were assessed. A systematic literature search was conducted and the articles found were analyzed and divided into categories based on specific communication skills taught and type of learning activity used. Oral interpersonal communication skills targeted at patients were the most common skill-type described, followed by clinical writing skills. Common teaching methods included simulated and standardized patient interactions and pharmacy practice experience courses. Most educational interventions were assessed by subjective measures. Many interventions were described as fragments, in isolation of other learning activities that took place in a course, which impedes complete analysis of study results. To succeed in communication training, integration between different learning activities and progression within pharmacy educations are important.